The Hepatoprotective and Anti-Nephrotoxic Potential of Methanolic Extract of a Polyherbal Preparation in CCl4-Induced Liver Injury Model of Wistar Rats. Issue 3 (20th September 2022) - Boota, Muhammad; Shah, Syed Muhammad Ali; Rashid, Abid; Akram, Muhammad; Ayaz, Sultan; Mustafa, Imtiaz; Nisar, Jaweria; Nisar, Zonaira
The liver and kidneys are the vital organs of the body and perform important life-sustaining functions in the body. Synthetic drugs used in the treatment of liver and kidney diseases are sometimes inadequate and can lead to serious side effects. Medicinal herbs and plants were used to combat diseases for a long time and combination therapy is preferred over single plant therapy. In the current study, the Asparagus racemosus, Mucuna pruriens, Anacyclus pyrethrum, and Tribulus terrestris polyherbal preparation (PHP) was selected to evaluate its hepatoprotective, antioxidant, and anti-nephrotoxic potential. The methanolic extract of PHP was prepared following standard protocols. Fifty-six albino rats were divided into 7 groups (n = 8). The negative control (NC) having the healthy rats and the remaining 6 groups were induced liver toxicity by intraperitoneally injecting 0.5 mL/kg of 50% CCl4 in olive oil. Group 2 was positive control and group 3 and 4 received silymarin standard drug at the dose of 100 and 200 mg/kg body weight. Groups 5, 6, and 7 (PHP-1, PHP-2, PHP-3) were the liver-damaged rats receiving the PHP at a dose of 50, 100, and 150 mg/kg body weight. Blood samples were collected at 21 of the trial, to evaluate oxidative stress, hepatoprotective and anti-nephrotoxic potential. Results of liver function tests revealed significant ( P < .05) hepatoprotective activities of PHP after intoxication with CCl4 of albino rats as compared to standard groups. Moreover, results of renal functions also showed that PHP has a significant ( P < .05) restoring the capacity of blood urea, creatinine, and uric acid in intoxicated rats as compared with the control group. The PHP also reduced the oxidative stress in the treatment groups by increasing the total antioxidant capacity and reducing the total oxidative status. It can be concluded that selected medicinal plants have a potential role in the management of liver and kidney disorders. So, by running the clinical trial on a large scale and by isolating the phytochemical constituents responsible for hepatoprotective and nephroprotective activities, locally prepared drugs could be developed to manage liver and renal disorders.